Molecular Validation of Chondrogenic Differentiation and Hypoxia Responsiveness of Platelet-Lysate Expanded Adipose Tissue–Derived Human Mesenchymal Stromal Cells. (July 2017) - Galeano-Garces, Catalina; Camilleri, Emily T.; Riester, Scott M.; Dudakovic, Amel; Larson, Dirk R.; Qu, Wenchun; Smith, Jay; Dietz, Allan B.; Im, Hee-Jeong; Krych, Aaron J.; Larson, A. Noelle; Karperien, Marcel; et al.
Objective: To determine the optimal environmental conditions for chondrogenic differentiation of human adipose tissue–derived mesenchymal stromal/stem cells (AMSCs). In this investigation we specifically investigate the role of oxygen tension and 3-dimensional (3D) culture systems. Design: Both AMSCs and primary human chondrocytes were cultured for 21 days in chondrogenic media under normoxic (21% oxygen) or hypoxic (2% oxygen) conditions using 2 distinct 3D culture methods (high-density pellets and poly-ε-caprolactone [PCL] scaffolds). Histologic analysis of chondro-pellets and the expression of chondrocyte-related genes as measured by reverse transcriptase quantitative polymerase chain reaction were used to evaluate the efficiency of differentiation. Results: AMSCs are capable of expressing established cartilage markers including COL2A1, ACAN, and DCN when grown in chondrogenic differentiation media as determined by gene expression and histologic analysis of cartilage markers. Expression of several cartilage-related genes was enhanced by low oxygen tension, including ACAN and HAPLN1. The pellet culture environment also promoted the expression of hypoxia-inducible cartilage markers compared with cells grown on 3D scaffolds. Conclusions: Cell type–specific effects of low oxygen and 3D environments indicate that mesenchymal cell fate and differentiation potential is remarkably sensitive to oxygen. Genetic programming of AMSCs to a chondrocytic phenotype is effective under hypoxic conditions as evidenced by increased expression of cartilage-related biomarkers and biosynthesis of a glycosaminoglycan-positive matrix. Lower local oxygen levels within cartilage pellets may be a significant driver of chondrogenic differentiation.